Migration of Sparganosis from the Brain to the Cervical Spinal Cord - Jang, Se Youn; Kim, Choong Hyun (Journal of Korean Neurosurgical Society, 2012)
Central nervous system (CNS) sparganosis is a rare parasitic infestation caused by ingestion of the raw or inadequately cooked snakes or frogs. Sparganum is well known for its ability of migrating though the tissue, therefore, it can cause various neurological symptoms if it involves neurological systems. A 51-year-old male patient visited our department of neurosurgery complaining of the motor weakness and radiating pain on both upper extremities over 4 months. He had a history of ingesting raw snakes untill his late twenties. The magnetic resonance (MR) images of cervical spine revealed an intramedullary ill-defined enhancing lesion with the aggregated cysts in the upper cervical spinal cord. Under presumptive diagnosis of sparganosis, we took brain MR image. The brain MR images revealed the signal change in right fronto-temporal lobe suggesting the trajectory of parasitic migration via ventricular systems. He underwent a midline myelotomy and granuloma removal followed by the posterior laminoplasty. Pathologic findings showed inflammatory changes and necrosis with keratinized tissue suggesting the CNS sparganosis. We report an uncommon case of CNS sparganosis migrated from the brain to the spinal cord with literature review.